One, two, three [videorecording (DVD)] - Cagney, James, 1899-1986; Buchholz, Horst, 1933-2003; Tiffin, Pamela; Francis, Arlene (KL studio classics., 2017)
In West Berlin during the Cold War, a Coca-Cola executive is given the task of taking care of his boss' socialite daughter.